When Celebration Becomes Arrhythmia: Recurrence of Alcohol-Induced Paroxysmal Atrial Fibrillation in a Young Adult - Gonçalves, Mauer; Vicente, Miguel; Nunes, Rosalina; Merite, Tshimbalanga; David, Catarina; Lourenço, Preciosa; Lucas, Evander; Katumua, Leonor André; Banzaga, Elizabeth; Catembula, Joel; Morais, Humberto (Brazilian Journal of Case Reports, 2026)
Atrial fibrillation is the most common sustained arrhythmia and may occur in young individuals without structural heart disease when triggered by reversible factors. Alcohol consumption is a well-established precipitant, particularly in the context of binge drinking, known as Holiday Heart Syndrome. We report the case of a 43-year-old man without cardiovascular risk factors who presented to the emergency department with palpitations lasting approximately 48 hours following acute alcohol binge intake during New Year celebrations. Electrocardiography confirmed atrial fibrillation with controlled ventricular response. Transthoracic echocardiography demonstrated normal cardiac chambers and preserved biventricular systolic function. Laboratory evaluation, including thyroid function and serum electrolytes, was unremarkable. Rate control with bisoprolol was initiated, followed by spontaneous conversion to sinus rhythm within 48 hours. Given a CHA₂DS₂-VA score of 0, no anticoagulation was indicated. This case highlights alcohol-induced atrial fibrillation as a reversible arrhythmogenic condition and reinforces the importance of lifestyle modification in preventing recurrence.